Schlimm, Dirk, "Pasch’s Empiricism as Methodological Structuralism." In: Erich H. Reck und Georg Schiemer (eds.), The Prehistory of Mathematical Structuralism, Oxford: University Press 2020, 88–105 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.01017)

Bellomo, Anna und Guillaume Massas, Bolzano’s Mathematical Infinite. The Review of Symbolic Logic 16, No. 1 (2023), 59–113 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1515.01010)

Tschirk, Wolfgang, Vom Universum des Denkens. Eine Geistesgeschichte der Logik, Springer: Berlin 2022 - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1508.03007)

Herrmann, Kay (Hg.), Grete Henry-Hermann: Philosophie – Mathematik – Quantenmechanik. Texte zur Naturphilosophie und Erkenntnistheorie, mathematisch-physikalische Beiträge sowie ausgewählte Korrespondenz aus den Jahren 1925 bis 1982. Springer VS: Wiesbaden 2019, xv + 664 S - Peckhaus, Volker (Zentralblatt für Mathematik und ihre Grenzgebiete Zbl 1506.01002)

SIG: Adaptivität und Adaptive Lehrkompetenz grundschulpädagogisch und (fach-)didaktisch reloaded - Reh, Anne; Schroeder, René; Miller, Susanne; Blumberg, Eva; Kottmann, Brigitte; Thevißen, Max

On the Dynamical Hierarchy in Gathering Protocols with Circulant Topologies - Gerlach, Raphael; von der Gracht, Sören; Dellnitz, Michael (arXiv:2305.06632)
In this article we investigate the convergence behavior of gathering protocols with fixed circulant topologies using tools form dynamical systems. Given a fixed number of mobile entities moving in the Euclidean plane, we model a gathering protocol as a system of ordinary differential equations whose equilibria are exactly all possible gathering points. Then, we find necessary and sufficient conditions for the structure of the underlying interaction graph such that the protocol is stable and converging, i.e., gathering, in the distributive computing sense by using tools from dynamical systems. Moreover, these tools allow for a more fine grained analysis in terms of speed of convergence in the dynamical systems sense. In fact, we derive a decomposition of the state space into stable invariant subspaces with different convergence rates. In particular, this decomposition is identical for every (linear) circulant gathering protocol, whereas only the convergence rates depend on the weights in interaction graph itself.
Keywords: Dynamical Systems; Coupled Systems; Distributed Computing; Robot Swarms; Autonomous Mobile Robots; Gathering

Politisierung von Jugend – Zur Einführung in den Band - Dahmen, Stephan; Demir, Zeynep; Ertugul, Baris; Kloss, Daniela; Ritter, Bettina (Politisierung der Jugend)

Politisierung von Jugend

Empirische Zugänge zu organisational kontextualisierter Professionalität - Dahmen, Stephan; Henn, Sarah; Ritter, Bettina; Mohr, Simon (Sozialpädagogische Professionalisierung in der Krise?)

Hydrodynamic and Non-hydrodynamic Excitations in Kinetic Theory -- A Numerical Analysis in Scalar Field Theory - Ochsenfeld, Stephan; Schlichting, Sören (arXiv:2308.04491)
Viscous hydrodynamics serves as a successful mesoscopic description of the Quark-Gluon Plasma produced in relativistic heavy-ion collisions. In order to investigate, how such an effective description emerges from the underlying microscopic dynamics we calculate the hydrodynamic and non-hydrodynamic modes of linear response in the sound channel from a first-principle calculation in kinetic theory. We do this with a new approach wherein we discretize the collision kernel to directly calculate eigenvalues and eigenmodes of the evolution operator. This allows us to study the Green's functions at any point in the complex frequency space. Our study focuses on scalar theory with quartic interaction and we find that the analytic structure of Green's functions in the complex plane is far more complicated than just poles or cuts which is a first step towards an equivalent study in QCD kinetic theory.

Wo lässt es sich im Universum leben? Eine Reise zu großen Sternen und kleinen Planeten - Hohmann, Sascha (Außerirdisches Leben)
Fast 5.000 Planeten in anderen Sternensystemen wurden inzwischen detektiert. Aber ist die Erde der einzige Planet, auf dem Leben möglich wäre? Kommt es dabei nur auf flüssiges Wasser und damit die Temperatur auf dem Planeten an oder gibt es noch andere Bedingungen, die Planet und Stern erfüllen müssen? Und warum sind die meisten bisher gefundenen Planeten dafür ziemlich ungeeignet? Diese und weitere Fragen sollen hier beantwortet werden.

Untersuchung des Einflusses von Relativverschiebungen während der Aushärtung auf die mechanischen Eigenschaften von Klebverbindungen - Beule, Felix; Teutenberg, Dominik; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)

Himmelskörper mit Geometrie - Hohmann, Sascha (Der Mathematikunterricht)

Experimentelle Untersuchung des Ermüdungsverhaltens von strukturellen Klebverbindungen und Berechnung der Lebensdauer unter Berücksichtigung der Spannungsanisotropie - Tews, Karina; Çavdar, Serkan; Meschut, Gerson (Klebtechnische Doktorandenseminare 2020 - 2022)

Intersektionalität und erzählte Welten. Fachwissenschaftliche und fachdidaktische Perspektiven auf Literatur und Medien
Der vorliegende Band versammelt intersektionale literaturwissenschaftliche und -didaktische Fallstudien aus unterschiedlichen Philologien und bietet so ein Prisma der Erforschung literarischer Repräsentationen des Zusammenspiels von einander verschärfenden bzw. abschwächenden Diskriminierungskategorien. Die Einzelbeiträge präsentieren kritische Reflexionen und Modifizierungen verschiedener Positionen der intersektionalen Forschung sowie Beispiele für die vielfältige Ausgestaltung intersektional orientierter Textanalyse auf theoretischer und methodischer Ebene. Da wissenschaftliche und literarische ebenso wie zeitgenössische und historische Texte in verschiedenen Sprachen (Englisch, Deutsch, Italienisch, Niederländisch, Spanisch etc.) aufgegriffen werden, zeigt der Band auf, dass Machtstrukturen in unterschiedlichen kulturellen Kontexten Analogien aufweisen, deren Analyse von Differenzierungen verschiedener Herrschaftsstrukturen profitiert.
Keywords: Intersektionalität; Literaturwissenschaft; Literaturunterricht; Klassenlektüre; Auswahl; Textanalyse; Literatur; Erzähltheorie; Machtstruktur; Diskriminierung; Geschlechterrolle; Geschlechterverhältnis; Geschlechtsidentität; Rassismus; Soziale Klasse; Othering; Feminismus

Serielles Erzählen kolonialer Rhetoriken. Ein diskursreflexives Unterrichtsmodell an der Schnittstelle von literaturunterrichtlichem und literaturmusealem Lernen - Kißling, Magdalena (Diversität und Darstellung. Zugehörigkeit und Ausgrenzung im Literaturmuseum und in den Literaturwissenschaften)

Memory Gym: Towards Endless Tasks to Benchmark Memory Capabilities of Agents - Pleines, Marco; Pallasch, Matthias; Zimmer, Frank; Preuss, Mike (arXiv:2309.17207)
Memory Gym presents a suite of 2D partially observable environments, namely Mortar Mayhem, Mystery Path, and Searing Spotlights, designed to benchmark memory capabilities in decision-making agents. These environments, originally with finite tasks, are expanded into innovative, endless formats, mirroring the escalating challenges of cumulative memory games such as ``I packed my bag''. This progression in task design shifts the focus from merely assessing sample efficiency to also probing the levels of memory effectiveness in dynamic, prolonged scenarios. To address the gap in available memory-based Deep Reinforcement Learning baselines, we introduce an implementation that integrates Transformer-XL (TrXL) with Proximal Policy Optimization. This approach utilizes TrXL as a form of episodic memory, employing a sliding window technique. Our comparative study between the Gated Recurrent Unit (GRU) and TrXL reveals varied performances across different settings. TrXL, on the finite environments, demonstrates superior sample efficiency in Mystery Path and outperforms in Mortar Mayhem. However, GRU is more efficient on Searing Spotlights. Most notably, in all endless tasks, GRU makes a remarkable resurgence, consistently outperforming TrXL by significant margins. Website and Source Code: https://github.com/MarcoMeter/endless-memory-gym/

Wahrnehmen von Missverhältnissen. Inkongruenzkomik in Fernsehserien zur Förderung literarischen Lernens - Kißling, Magdalena (Was gibt es da noch zu lachen? Komik in Texten und Medien der Gegenwartskultur in litera-turdidaktischer Perspektive)

Game of Thrones: (Re)arrangend gender roles on screen? - Eremin, Oxana (Bulletin-Texte 47, GenderErträgeV. Texts from the SVR Student Lecture Series)

Towards active learning: A stopping criterion for the sequential sampling of grain boundary degrees of freedom - Schmalofski, Timo; Kroll, Martin; Dette, Holger; Janisch, Rebecca (arXiv:2302.01603)
Many materials processes and properties depend on the anisotropy of the energy of grain boundaries, i.e.~on the fact that this energy is a function of the five geometric degrees of freedom (DOF) of the interface. To access this parameter space in an efficient way and to discover energy cusps in unexplored regions, a method was recently established, which combines atomistic simulations with statistical methods 10.1002/adts.202100615. This sequential sampling technique is now extended in the spirit of an active learning algorithm by adding a criterion to decide when the sampling has advanced enough to stop. In this instance, two parameters to analyse the sampling results on the fly are introduced: the number of cusps, which correspond to the most interesting and important regions of the energy landscape, and the maximum change of energy between two sequential iterations. Monitoring these two quantities provides valuable insight into how the subspaces are energetically structured. The combination of both parameters provides the necessary information to evaluate the sampling of the 2D subspaces of grain boundary plane inclinations of even non-periodic, low angle grain boundaries. With a reasonable number of data points in the initial design, only a few appropriately chosen sequential iterations already improve the accuracy of the sampling substantially and unknown cusps can be found within a few additional sequential steps.

Pre-Equilibrium Evolution of Conserved Charges with ICCING Initial Conditions - Carzon, Patrick; Martinez, Mauricio; Jacquelyn Noronha-Hostler, Jacquelyn Noronha-Hostler; Plaschke, Philip; Schlichting, Soeren; Sievert, Matthew (arXiv:2301.04572)
Heavy-ion collisions can be well described through relativistic viscous hydrodynamics, but questions still remain when hydrodynamics is applicable because the initial state may begin very far-from-equilibrium. Thus, a pre-equilibrium evolution phase is used to bridge the gap between the initial state and hydrodynamics. K$φ$MP$φ$ST is one such pre-equilibrium model that propagates the energy-momentum tensor by decomposing it into the background and fluctuations around that background, whose evolution is captured by Green's functions. We extend this formalism to include conserved charges and calculate the corresponding non-equilibrium Green's functions in the relaxation time approximation. The ICCING algorithm initializes conserved charges in the initial state by sampling $g → q\bar{q}$ splitting probabilities and is, thus, perfectly positioned to implement Green's functions for charge propagation. We show that this method alters the initial state charge geometries and is applicable in central to mid-central collisions.

Implications of Algorithmic Wage Setting on Online Labor Platforms: a Simulation-Based Analysis∗ - Dawid, Herbert; Harting, Philipp; Neugart, Michael (SSRN Electronic Journal)
Keywords: General Earth and Planetary Sciences; General Environmental Science

Universality of energy-momentum response in kinetic theories - Du, Xiaojian; Ochsenfeld, Stephan; Schlichting, Sören (arXiv:2306.09094)
We study the response of the energy-momentum tensor in several kinetic theories, from the simple relaxation time approximation (RTA) to Quantum Chromodynamics (QCD). Irrespective of the differences in microscopic properties, we find a remarkable degree of universality in the response functions from conformal theories. We find that the response to scalar perturbations in kinetic theory can be effectively described by a pair of one hydrodynamic sound mode and one non-hydrodynamic mode. We find that even beyond the range of validity of hydrodynamics, the energy-momentum response in position space can be effectively described by one single mode with non-trivial dispersion relation and residue.

Ultrafast two-colour X-ray emission spectroscopy reveals excited state landscape in a base metal dyad - Bauer, Matthias (Ultrafast two-colour X-ray emission spectroscopy reveals excited state landscape in a base metal dyad)

Optogenetics reveals paradoxical network stabilizations in hippocampal CA1 and CA3 - de Jong, Laurel Watkins; Nejad, Mohammadreza Mohagheghi; Yoon, Euisik; Cheng, Sen; Diba, Kamran (Current Biology)

Investigation of the Compatibility between Warheads and Peptidomimetic Sequences of Protease Inhibitors—A Comprehensive Reactivity and Selectivity Study - Müller, Patrick; Meta, Mergim; Meidner, Jan Laurenz; Schwickert, Marvin; Meyr, Jessica; Schwickert, Kevin; Kersten, Christian; Zimmer, Collin; Hammerschmidt, Stefan Josef; Frey, Ariane; Lahu, Albin; de la Hoz-Rodríguez, Sergio; et al. (International Journal of Molecular Sciences)
Covalent peptidomimetic protease inhibitors have gained a lot of attention in drug development in recent years. They are designed to covalently bind the catalytically active amino acids through electrophilic groups called warheads. Covalent inhibition has an advantage in terms of pharmacodynamic properties but can also bear toxicity risks due to non-selective off-target protein binding. Therefore, the right combination of a reactive warhead with a well-suited peptidomimetic sequence is of great importance. Herein, the selectivities of well-known warheads combined with peptidomimetic sequences suited for five different proteases were investigated, highlighting the impact of both structure parts (warhead and peptidomimetic sequence) for affinity and selectivity. Molecular docking gave insights into the predicted binding modes of the inhibitors inside the binding pockets of the different enzymes. Moreover, the warheads were investigated by NMR and LC-MS reactivity assays against serine/threonine and cysteine nucleophile models, as well as by quantum mechanics simulations.
Keywords: Inorganic Chemistry; Organic Chemistry; Physical and Theoretical Chemistry; Computer Science Applications; Spectroscopy; Molecular Biology; General Medicine; Catalysis

Apologie für das Nebensächliche. Prinzipien einer intersektional orientierten Unterrichtsmodel-lierung am Beispiel von Aneignungsperspektiven zu einer jugendpopulären Fernsehserie - Kißling, Magdalena (Rassismussensibler Literaturunterricht – Grundlagen, Dimensionen, Herausforderungen, Möglichkeiten)

Differenzkonstruktionen in Explikation und Beiläufigkeit. Vergleichende Betrachtungen zur Wirkungsästhetik bei Fünftklässler:innen hinsichtlich unterschiedlichen kinderliterarischen Erzählens von Diversität - Kißling, Magdalena ("So viel Größenwahn muss sein!" Kinderliteratur - Schule - Gesellschaft)

Diskriminierungssensible Methoden. Neue Lernwege im kulturwissenschaftlich ausgerichteten Literaturunterricht - Kißling, Magdalena (Neue Perspektiven einer kulturwissenschaftlich orientierten Literaturdidaktik)

Hannah Arendt and Politics - Robaszkiewicz, Maria Anna; Weinman, Michael D.

Dequantizing the Quantum Singular Value Transformation: Hardness and Applications to Quantum Chemistry and the Quantum PCP Conjecture - Gharibian, Sevag; Le Gall, François (SIAM Journal on Computing)
Keywords: General Mathematics; General Computer Science

Untersuchung der Dichtheitseigenschaften hybridgefügter Mischbauverbindungen für den Einsatz in Batterieghäusen für Elektrofahrzeuge - Schmolke, Tobias; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

A Marxist-Humanist Perspective on Stuart Hall's Communication Theory - Fuchs, Christian (Theory and Society)

Experimentelle Untersuchung der Dämpfungseigenschaften geklebter Strukturen unter dynamischer Beanspruchung - Göddecke, Johannes; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

Effizientes Lösen von Klebverbindungen in der Fahrzeuginstandsetzung - Chudalla, Nick; Meschut, Gerson (11. - 13- Doktorandenseminar Klebtechnik)

„Wir fahren jetzt nicht mit’m Mercedes vor, wenn man sich nachher eigentlich nur ‘n Polo leisten kann.“ Vorstellungen von Transfer in Theorie und Praxis der Beruflichen Bildung und ihre Implikationen - Daniel-Söltenfuß, Desiree

Zum Verständnis von Innovation und Transfer in einer vernetzten Berufsbildungspraxis. Ergebnisse einer übergreifenden Interviewstudie - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

Optimizing the Streaming of Sensor Data with Approximate Communication - Sadeghi-Kohan, Somayeh; Reimer, Jan Dennis; Hellebrand, Sybille; Wunderlich, Hans-Joachim (IEEE Asian Test Symposium (ATS'23), October 2023)

„Go with the flow?!“ Einblicke in Forschungsansatz und erste Ergebnisse des Begleitforschungsprojekts ITiB - Daniel-Söltenfuß, Desiree; Kückmann, Marie-Ann

Packings and Steiner systems in polar spaces - Schmidt, Kai-Uwe; Weiß, Charlene (Combinatorial Theory)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-Steiner system in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $n$-spaces such that each totally isotropic $t$-space is contained in exactly one member of $Y$. Nontrivial examples are known only for $t=1$ and $t=n-1$. We give an almost complete classification of such $t$-Steiner systems, showing that such objects can only exist in some corner cases. This classification result arises from a more general result on packings in polar spaces.

Existence of small ordered orthogonal arrays - Schmidt, Kai‐Uwe; Weiß, Charlene (Journal of Combinatorial Designs)
We show that there exist ordered orthogonal arrays, whose sizes deviate from the Rao bound by a factor that is polynomial in the parameters of the ordered orthogonal array. The proof is nonconstructive and based on a probabilistic method due to Kuperberg, Lovett and Peled.

Linear programming bounds in classical association schemes - Weiß, Charlene
Digital communications relies heavily on the usage of different types of codes. Prominent codes nowadays are rank-metric codes and subspace codes - the q-analogs of binary codes and binary codes with constant weight. All these codes can be viewed as subsets of classical association schemes. A central coding-theoretic problem is to derive upper bounds for the size of codes. This thesis investigates Delsartes powerful linear program whose optimum is precisely such a bound for codes in association schemes. The linear programs for binary codes and binary constant-weight codes have been extensively studied since the 1970s, but their optimum is still unknown. We determine in a unified way the optimum of the linear program in several ordinary q-analogs as well as in their affine counterparts. In particular, bounds and constructions for codes in polar spaces are established, where the bounds are sharp up to a constant factor in many cases. Moreover, based on these results, an almost complete classification of Steiner systems in polar spaces is provided by showing that they could only exist in some corner cases.

Nontrivial $t$-designs in polar spaces exist for all $t$ - Weiß, Charlene (arXiv:2311.08288)
A finite classical polar space of rank $n$ consists of the totally isotropic subspaces of a finite vector space over $\mathbb{F}_p$ equipped with a nondegenerate form such that $n$ is the maximal dimension of such a subspace. A $t$-$(n,k,λ)$ design in a finite classical polar space of rank $n$ is a collection $Y$ of totally isotropic $k$-spaces such that each totally isotropic $t$-space is contained in exactly $λ$ members of $Y$. Nontrivial examples are currently only known for $t≤ 2$. We show that $t$-$(n,k,λ)$ designs in polar spaces exist for all $t$ and $p$ provided that $k>\frac{21}{2}t$ and $n$ is sufficiently large enough. The proof is based on a probabilistic method by Kuperberg, Lovett, and Peled, and it is thus nonconstructive.

"Fotonotizen". documenta fifteen - Autsch, Sabiene (Impulse 6. Texte und Bilder zur Kunstvermittlung: ABHÄNGEN. Ein interdisziplinäres Projekt zur documenta fifteen (2022))

"More human than human.“ – Biopolitik und Geschlecht in Alex Garlands Ex Machina - Puscher, Sahra (Biopolitik(en) in Literatur, Film und Serie. Aushandlungs- und Reflexionsräume vom 18. Jahrhundert bis heute)

Assessment of long-term dietary cadmium exposure in children in Germany: Does consideration of data from total diet studies reduce uncertainties from food monitoring programmes? - Kolbaum, AE; Jung, C; Jaeger, A; Libuda, Lars; Lindtner, O (Food Chem Toxicol)

SEMOK-1-2: Selbstwahrnehmung motorischer Basiskompetenzen in der ersten und zweiten Primarschulklasse. Manual - Bretz, Kathrin; Strotmeyer, Anne; Herrmann, Christian
Um die Selbstwahrnehmung motorischer Basiskompetenzen bei Kindern der 1. und 2. Klasse zu erfassen, wurde ein illustriertes Instrument entwickelt. Das Instrument orientiert sich am MOBAK-1-2 Instrument, mit welchem die motorischen Basiskompetenzen von Kindern getestet werden. Das Manual enthält die Instruktionen sowie die illustrieren Antwortoptionen und Testaufgaben.

Designbasierte Forschung in der beruflichen Bildung:Perspektiven aus Wissenschaft, Praxis und Politik. - Ertl, Hubert; Kremer, H.-Hugo; Kundisch, Heike; Sloane, Peter F. E. (Wissenschaft trifft Praxis - Designbasierte Forschung in der beruflichen Bildung.)
Designbasierte Forschung umfasst verschiedene Ausprägungsformen von Forschungsprozessen, die auf die Entwicklung und Implementation von Innovationen abzielen. Mit der Anwendung von designbasierten Ansätzen haben Forscherinnen und Forscher den Anspruch, sich an der Lösung praktischer Problemlagen zu beteiligen; dies ist ein wichtiger Ausgangspunkt für die Anlage von Forschungsprozessen und -programmen. Häufig geht es um bisher wenig strukturierte, aktuelle Probleme in der Berufsbildungspraxis, was wiederum bedeutsam für das Aufeinandertreffen und die Zusammenarbeit von Wissenschaft und Praxis ist. Der vorliegende Band nimmt die Vielfalt designbasierter Forschung auf und dokumentiert, ergänzt durch Visualisierungen, die Beiträge des AG BFN Forums „Wissenschaft trifft Praxis – Designbasierte Forschung in der beruflichen Bildung“, welches in einem digitalen Format an der Universität Paderborn stattfand.

Recalibration of limits to growth: An update of the World3 model - Nebel, Arjuna; Kling, Alexander; Willamowski, Ruben; Schell, Tim (Journal of Industrial Ecology)
Abstract After 50 years, there is still an ongoing debate about the Limits to Growth (LtG) study. This paper recalibrates the 2005 World3‐03 model. The input parameters are changed to better match empirical data on world development. An iterative method is used to compute and optimize different parameter sets. This improved parameter set results in a World3 simulation that shows the same overshoot and collapse mode in the coming decade as the original business as usual scenario of the LtG standard run. The main effect of the recalibration update is to raise the peaks of most variables and move them a few years into the future. The parameters with the largest relative changes are those related to industrial capital lifetime, pollution transmission delay, and urban‐industrial land development time.
Keywords: General Social Sciences; General Environmental Science

Wie wir die mittlere Führungsebene als Transformationsbegleiter:innen an Schulen stärken können - Kundisch, Heike (Magazin des Forum Bildung Digitalisierung)